The dietary effect of milk sphingomyelin on the lipid metabolism of obese/diabetic KK-Ay mice and wild-type C57BL/6J mice. Issue 9 (9th August 2016) - Yamauchi, Ippei; Uemura, Mariko; Hosokawa, Masashi; Iwashima-Suzuki, Ai; Shiota, Makoto; Miyashita, Kazuo
Abstract : Purified milk sphingomyelin (SM) was obtained from lipid concentrated butter serum (LC-BS) by successive separations involving solvent fractionation, selective saponification, and silicic acid column chromatography. Abstract : Purified milk sphingomyelin (SM) was obtained from lipid concentrated butter serum (LC-BS) by successive separations involving solvent fractionation, selective saponification, and silicic acid column chromatography. The SM obtained was given to obese/diabetic KK- A y mice and wild-type C57BL/6J mice. SM supplementation significantly increased fecal lipids paralleled with a decrease in non-HDL cholesterol levels in the serum and neutral lipids and in cholesterol levels in the livers of KK- A y mice. The reduction of liver lipid levels also resulted in a decrease in the total fatty acid content of the KK- A y mice livers, while n-3 fatty acids derived from the conversion of α-linolenic acid (18:3n-3) increased due to SM supplementation. In contrast to the KK- A y mice, little change in the serum and liver lipids was observed in wild-type C57BL/6J mice. The present study suggests that SM may be effective only in subjects with metabolic disorders.